Corticosteroid induced remission of oesophageal involvement in mixed connective tissue disease. Issue 679 (May 1982) - Pines, Amos; Goldhammer, Ehud; Kaplinsky, Naomi; Bregman, Joseph; Frankl, Otto
Abstract : Oesophageal involvement is known to be one of the most severe and resistant manifestations of connective tissue diseases, mainly progressive systemic sclerosis (PSS). A patient who had manifestations of systemic lupus erythematosus, PSS and polymyositis is described. Since some features of mixed connective tissue disease (MCTD) respond to corticosteroid treatment, fluocortolone was administered and both clinical and radiological remission of the oesophageal involvement were observed. At the same time, there was also a marked improvement of the cutaneous lesions. In view of the described observation, it seems advisable to try this treatment for oesophageal manifestations of MCTD.